2015
DOI: 10.1111/jne.12236
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin Signalling on Food Reward: A Salient Link Between the Gut and the Mesolimbic System

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.'Hunger is the best spice' is an old and wise saying that acknowledges the fact that almost any food tastes better when we are hungry. The neurobiological underpinnings of this lore include activation of the brain's reward system and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
121
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(130 citation statements)
references
References 151 publications
3
121
0
6
Order By: Relevance
“…Thus, currently existing evidence suggests that the ghrelin/GOAT/GHSR1a system is closely linked to pathways involved in reward aspects of food intake, additionally and partially separated from those determining food intake initiation. 35 Mediation of this eating behaviour response by ghrelin is accomplished through the dopaminergic neural network extending from the ventral tegmental area and other brain nuclei and finally resulting in food intake depending on its reward aspects. 36 Hence, at the mesolimbic level, ghrelin would produce increased hedonic aspects of eating and increase motivation to seek and procure food, initiating anticipatory activity and foraging behaviours.…”
Section: Ghrelin -A Peripheral Orexigenic Peptide With Central Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, currently existing evidence suggests that the ghrelin/GOAT/GHSR1a system is closely linked to pathways involved in reward aspects of food intake, additionally and partially separated from those determining food intake initiation. 35 Mediation of this eating behaviour response by ghrelin is accomplished through the dopaminergic neural network extending from the ventral tegmental area and other brain nuclei and finally resulting in food intake depending on its reward aspects. 36 Hence, at the mesolimbic level, ghrelin would produce increased hedonic aspects of eating and increase motivation to seek and procure food, initiating anticipatory activity and foraging behaviours.…”
Section: Ghrelin -A Peripheral Orexigenic Peptide With Central Actionmentioning
confidence: 99%
“…36 Hence, at the mesolimbic level, ghrelin would produce increased hedonic aspects of eating and increase motivation to seek and procure food, initiating anticipatory activity and foraging behaviours. 35 Based on these aspects, some researchers have proposed the clinical use of ghrelin in cases in which increased levels of food intake may be beneficial, such as elderly patients with nutritional deficiencies 37 or with anorexia associated with different consumption diseases. 38 Ghrelin is considered an orexigenic signal (gutbrain) for the control of appetite and energy balance in healthy individuals.…”
Section: Ghrelin -A Peripheral Orexigenic Peptide With Central Actionmentioning
confidence: 99%
“…GHRL is a peptide hormone basically synthesized in the gastrointestinal tract that is octanoylated by ghrelin O-acyl transferase. This octanoylation is essential for binding to the growth hormone secretagogue receptor (GHS-R1a) present in several locations, including hypothalamic neurons (Perello & Dickson 2015, Al Massadi et al 2015. The binding elicits an orexigenic response through enhanced stimulation of NPY/AgRP and decreased POMC/CART gene expression (Velásquez et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is well-known to regulate rewarding aspects of eating, thereby increasing food-seeking behavior (33,34). It has been found that intravenous administration of ghrelin increases the incentive value of food cues (35) and ghrelin has been associated with alcohol cravings (36), indicating a role of ghrelin in more "general" reward processing.…”
mentioning
confidence: 99%
“…To increase the specificity of our analyses, we focused on predefined regions of interest (ROIs) in the ventral striatum (VS) as well as lOFC and mOFC. Since ghrelin has been discussed as a potential "link" between fasting and increased reward behavior (42) by stimulating the mesolimbic reward circuitry (34), and has been found to enhance the response to food stimuli in various brain areas involved in the processing of food reward (43), we decided to primarily focus on ghrelin signaling.…”
mentioning
confidence: 99%